Characterization of groundwater quality destined for drinking water supply of Khenchela City (eastern Algeria) - Benrabah Samia; Attoui Badra; Hannouche Mani (Journal of Water and Land Development, 2016)
In spite of the abundance of water resources in the watershed of Khenchela region, the strong urban growth and the expansion of agricultural land resulted in a considerable increase in water needs. This fact exposed groundwater and surface vulnerability to an overlooked growing pollution.